Double and Single Yolked Duck Eggs: Their Contents and Dimensions Compared and the Mechanical Stimulation Hypothesis for Albumen Secretion Is Supported - Salamon , Attila; Kent, John P. (International Journal of Poultry Science, 2013)
The external dimensions, weight and contents (yolk, albumen, shell) of Double Yolked (DY) and Single Yolked (SY) eggs of the duck (Anas platyrhynchos domesticus) were measured and compared. The yolks in DY eggs did not differ in weight (p = 0.144), although each double yolk was significantly lighter than the yolk of a SY egg (p